Magnitude and predictors of pre-diabetes among adults in health facilities of Gondar city, Ethiopia: a cross-sectional study - Andargie, Tsegereda Abebe; Mengistu, Berhanu; Baffa, Lemlem Daniel; Gonete, Kedir Abdela; Belew, Aysheshim Kassahun (Frontiers in Public Health, 2023)
Introduction: Impaired glucose tolerance currently affects 374 million (7.5%) people worldwide; by 2030, this number is expected to be 454 million (8%). Urban inhabitants have an increased risk of developing pre-diabetes. Thus, the study aimed to assess the magnitude of pre-diabetes and associated factors among adults attending outpatient departments in Gondar city health facilities, Ethiopia. Method: From March 03 to April 18, 2020, institution-based cross-sectional study was conducted. Systematic random sampling technique was used to select 992 participants. Data were gathered using an interviewer-administered questionnaire, and fasting blood glucose was assessed using capillary blood. Bivariable and multivariable binary logistic regression analyses were fitted to check the association between independent variables and pre-diabetes. The level of statistical significance was declared at a p-value < 0.05. Results: The prevalence of pre-diabetes was 16.6% (95% CI 14.3%-18.8%). Age (AOR= 3.66, 95% CI (2.05, 6.52)), family history of diabetes mellitus (AOR= 3.46, 95% CI (2.16, 5.52)), waist circumference (AOR= 3.6, 95% CI (2.26, 5.88)), physical activity (AOR: 5.02, 95% CI (2.87, 8.77)), dietary diversity (AOR=3.07, 95% CI (1.95, 4.84)) and smoking (AOR= 2.9,95% CI (1.42, 6.05)) were factors associated with pre-diabetes. Conclusion: In our study, one in six adults in the health facilities were having pre-diabetes. Age, family history of diabetes, waist circumference, physical activity, dietary diversity, and smoking were factors associated with pre-diabetes. Therefore, it is recommended that adults should be educated on modifying their lifestyle including their diet and substantial care for the older adults should be enhanced.